The Influence of Ocean Topography on the Upwelling of Carbon in the Southern Ocean. Issue 19 (8th October 2021) - Brady, Riley X.; Maltrud, Mathew E.; Wolfram, Phillip J.; Drake, Henri F.; Lovenduski, Nicole S.
Abstract: The physical circulation of the Southern Ocean sets the surface concentration and thus air‐sea exchange of C O 2 . However, we have a limited understanding of the three‐dimensional circulation that brings deep carbon‐rich waters to the surface. Here, we introduce and analyze a novel high‐resolution ocean model simulation with active biogeochemistry and online Lagrangian particle tracking. We focus our attention on a subset of particles with high dissolved inorganic carbon (DIC) that originate below 1, 000 m and eventually upwell into the near‐surface layer (upper 200 m). We find that 71% of the DIC‐enriched water upwelling across 1, 000 m is concentrated near topographic features, which occupy just 33% of the Antarctic Circumpolar Current. Once particles upwell to the near‐surface layer, they exhibit relatively uniform p C O 2 levels and DIC decorrelation timescales, regardless of their origin. Our results show that Southern Ocean bathymetry plays a key role in delivering carbon‐rich waters to the surface. Plain Language Summary: The Southern Ocean is the only place in the world where ocean currents circle the globe without hitting land. Here, some of the strongest winds on the planet force water to flow west‐to‐east around Antarctica and bring water from kilometers deep up to the surface. These waters have traversed the deep ocean for centuries, and in that time have gathered large stores of carbon from dead algae that rain down from above. When this water is brought to the surface, it expels its large store of carbon to the atmosphere. This process is important for the carbon cycle, but has not been extensively studied. Here, we use a new ocean model simulation that estimates ocean carbon and follows virtual floats that flow around the ocean and measure simulated carbon levels. We use the model to figure out how deep carbon in the Southern Ocean reaches the surface. We find that a large fraction of the carbon that is brought up from depth to the surface occurs in a relatively small fraction of the Southern Ocean, near places with mountains on the sea floor. Our study demonstrates that mountains on the sea floor have an influence on the global carbon cycle. Key Points: We simulate the biogeochemical properties of online Lagrangian particles in the Southern Ocean Ocean bathymetry plays a disproportionate role in bringing deep, carbon‐rich water to the Southern Ocean surface All upwelled particles in the upper ocean exhibit relatively uniform pCO2 and rates of carbon transformation, regardless of their origin